Lower Body Temperature Independently Predicts Delayed Cerebral Infarction in the Elderly With Ruptured Intracranial Aneurysm - Lin, Hui; Wang, Haojie; Xu, Yawen; Lin, Zhangya; Kang, Dezhi; Zheng, Shufa; Yao, Peisen (Frontiers in Neurology, 2022)
Purpose: To assess the correlation between admission body temperature and delayed cerebral infarction in elderly patients with ruptured intracranial aneurysm (IA). Methods: Patients with ruptured IA diagnosed between 2012 and 2020 were retrospectively analyzed. Patients were divided into two groups based on presence of cerebral infarction after treatment: non-infarction group and infarction group. We compared the clinical characteristics, laboratory data, and methods used for IA treatment between two groups. Outcomes at 3 months after treatment were assessed using the modified Rankin Scale. Correlation between admission body temperature and cerebral infarction was assessed using Spearman’s rank correlation coefficient. The receiver operating characteristic (ROC) curve was used to assess the specificity and sensitivity of admission body temperature as a variable to distinguish between the infarction and non-infarction groups. Results: Four hundred and twenty-six patients with ruptured IA were enrolled. The infarction group and non-infarction group had 53 and 373 patients, respectively. Elderly patients with cerebral infarction (53/426 [12.4%]) had a lower body temperature at admission (p < 0.001), higher prevalence of hypertension (p = 0.051) and diabetes (p = 0.092), and higher rate of poor outcomes (p < 0.001). Multivariate logistic regression analysis showed admission body temperature is independently associated with cerebral infarction in these patients (odds ratio (OR) = 5.469, p < 0.001); however, hypertension (OR = 0.542, p = 0.056), diabetes (OR = 0.750, p = 0.465), and aneurysm size (OR = 0.959, p = 0.060) showed no association. Further, an inverse correlation between admission body temperature and incidence of cerebral infarction was observed in elderly patients with IA (Spearman’s r =-0.195, p < 0.001). ROC curve showed admission body temperature of 36.6 °C is the optimal cutoff value to distinguish between infarction and non-infarction groups. The area under the ROC curve was 0.669 (specificity, 64.15%; sensitivity, 81.50%; p < 0.001). Conclusions: Lower body temperature at admission (≤ 36.6 °C) is an independent predictor of delayed cerebral infarction in elderly patients after undergoing treatment for ruptured IA, thus, it could be a risk factor for adverse outcomes of IA. However, further large-scale clinical trials are required to confirm this finding.